Online system to improve the control of day tour reservations at Hotel Isla del Encanto (2022)
Day tour service is seen as an excellence business opportunity considering the fact that Cartagena receives plenty of tourist who want to visit the islands that make up the Corales delRosario National Natural Park. Tourists make their reservations by multiple mechanism, they look forward an unforgettable experience and as a hotel is our duty to make it a reality. However, complications may arise whensales agents receive the information manually. Therefore, the purpose of this research is to develop an online system which helps to channelthe information to have a better control of reservations.